Invasion Risk of Established and Horizon Non-Native Ants in the Mediterranean: A Screening for Italy - Enrico Schifani; Daniela Giannetto; Lorenzo Vilizzi (Insects)
Over five hundred non-native ant species have spread worldwide, including many that have severe effects on biodiversity, are serious economic pests, or threaten human health and agriculture. The number of species in the Mediterranean is steadily increasing, with Italy being a prominent example. We provide risk screenings for non-native ant species in Italy using a Terrestrial Species Invasiveness Screening Kit using current climate conditions and future predictions. The screened species consist of 15 established and 12 horizon taxa. The results highlight the threat posed by Linepithema humile and Solenopsis invicta, followed by Wasmannia auropunctata, Brachyponera chinensis, and Solenopsis geminata. The threat posed by other tropical invaders such as Anoplolepis gracilipes and Pheidole megacephala depends on climate change scenarios. The Palearctic non-native Lasius neglectus and Tetramorium immigrans species are recognized as intermediate threats, while most screened species are far less threatening. The biology and ecology of most non-native ant species remain scarcely documented. Among the established species, B. chinensis, L. humile, and S. invicta deserve the most attention, while W. auropunctata is rapidly spreading in neighboring countries. Detection is still often accidental and late compared to establishment. Most species first establish around urban areas, making citizen science a promising tool for biosurveillance.